Immediate Clinical Outcomes in Patients with Multi-Vessel Coronary Artery Disease and Left Ventricular Dysfunction following Off-Pump CABG (Medical Forum Monthly, 2021)
Objective: To determine the immediate clinical outcomes in patients with Multi-vessel coronary artery disease and left ventricular dysfunction following off-pump coronary artery bypass graft surgery.Study Design: A Prospective observational studyPlace and Duration of Study: This study was conducted at the department of Cardiac Surgery in Ch.Pervaiz Elahi Institute of Cardiology Multan from May 2019 to May 2021 for a period of two years.Materials and Methods: Eighty-nine patients who were treated with OPCAB were included as study participants. The patients who intraoperatively underwent on-pump CABG were excluded from the study. Procedures were performed by “consultant cardiothoracic surgeons”. The demographic variables of the patients were collected. Preoperative care was provided to the patient till the day of surgery. Proper technique of OPCABG was followed. The immediate clinical outcomes that included all the in-hospital outcomes till 30 days follow-up were recorded.Results: The prospective observational study included 89 participants. Among these 89 patients, 54% (48) were male and 46% (41) were female. The mean age and standard deviation were 58±8.2 & 60±8.5 of the male and female groups respectively. History of the patients revealed that 60% (53) were hypertensive, 61% (68) had a previous history of myocardial infarction, 16% (14) had peripheral vascular disease, 63% (56) were known cases of diabetes. Moreover, 45% (41) has a deranged lipid profile, 16% (14) had chronic kidney disease while 5% (4) had severe LV dysfunction. The mean hospital stay in days was reported as 4 ± 2 days while the mean time spent on a ventilator was recorded as 9.2 ± 7.8 hrs. It was seen that factors like post-operative atrial fibrillation, severe left ventricular dysfunction, and end-stage renal failure contributed to mortality. Among Postoperative outcomes stroke & sternal infections were witnessed in 2.24% (2), atrial fibrillation in 13.4% (12), and re-exploration was done in 2.24% (2) of cases. Septicemia occurred in 8.9% (8), 16.8% (15) patients were readmitted following CABG. Total 5 deaths were reported.Conclusion: In conclusion, off-pump CABG for patients with Multi-vessel coronary artery disease and left ventricular dysfunction had better in-hospital/immediate clinical outcomes with long-term survival rates.